Activation of RAW264.7 cells by PCp-I, a polysaccharide from Psoralea corylifolia L, through NF-κB/MAPK signalling pathway. (April 2021) - Wang, Honglin; Xu, Xiaoqing; Yin, Zhenhua; Wang, Mengke; Wang, Baoguang; Ma, Changyang; Wang, Jinmei; Kang, Wenyi
PCp-I is a polysaccharide isolated and identified from the Psoralea corylifolia L. by our research group. In this study, the immunomodulatory effects of PCp-I on RAW264.7 cells was evaluated. PCp-I could enhance the level of NO along with up-regulation of iNOS mRNA in RAW264.7 cells. The PCp-I could significantly up-regulate the mRNA expression of TNF- α and IL-6 in RAW264.7 cells, and then the expression of TNF- α, IL-6, ROS and the phagocytic activity were increased. Additionally, PCp-I could significantly up-regulate the phosphorylation level of p65, p38, ERK and JNK proteins, which proved that PCp-I could activate the macrophages by MAPKs and NF- κ B signalling pathway and the TLR4 may be one of the receptors of PCp-I regulate the RAW264.7 cells.